The Influence of Entrepreneurial Education, Entrepreneurial Self-Efficacy on Entrepreneurial Intention Mediated by Entrepreneurial Attitude in Students of Bengkulu University - Armelia Yundarti,; Nasution, (Jurnal Manajemen, 2026)
The role of entrepreneurship contributes significantly to driving the economic development of a country and can be one of the solutions to reduce unemployment in Indonesia. This study aims to determine the effect of entrepreneurial education and entrepreneurial self-efficacy on entrepreneurial intention with entrepreneurial attitude mediation in students of the University of Bengkulu. The sample used Slovin formula was 392 respondents who had taken entrepreneurship courses using nonprobability sampling techniques and the sampling technique used was purposive sampling. The data collection tool in this study was an online questionnaire for students of the University of Bengkulu. The tests carried out were validity, reliability and hypothesis testing with the help of SEM PLS (Partial Least Square) 4 software. Based on field research, the following results were obtained: (1) the effect of entrepreneurial education on entrepreneurial intention is not significant; (2) the effect of entrepreneurial self-efficacy on entrepreneurial intention is significantly positive; (3) the effect of entrepreneurial attitude on entrepreneurial intention is significantly positive; (4) The effect of entrepreneurial education on entrepreneurial attitude is significantly positive; (5) entrepreneurial self-efficacy on entrepreneurial attitude is significantly positive; (6) entrepreneurial attitude can mediate the influence of entrepreneurial education on entrepreneurial intention; (7) entrepreneurial attitude can mediate the influence of entrepreneurial self-efficacy on entrepreneurial intention.